WANITA SEBAGAI PENCARI NAFKAH UTAMA DI KARAWANG:PERSPEKTIF HUKUM KELUARGA ISLAM INDONESIA - Nira Arum Sari; Witia Oktaviani (LPPM STAI Muhammadiyah Probolinggo, 2025)
The obligation to provide financial support arises as a consequence of the marriage contract. In Islamic law, the primary responsibility for earning a livelihood lies with the husband. However, over time, this role has gradually shifted, especially as women increasingly participate in the workforce. Karawang ranks as the second highest region in Indonesia in terms of minimum wage (UMK), which attracts a large number of workers, including women, from various areas.This study aims to identify the factors that lead women to become the primary breadwinners in Karawang, analyze the implications of this role, and examine its legal status from the perspective of Islamic Family Law in Indonesia. The research employs a descriptive qualitative approach, collecting data through interviews via Google Forms with 18 female workers in Karawang who act as primary providers for their families. The findings reveal two key driving factors: external and internal. This dual role brings various implications, including economic impacts on the family, relationship conflicts, and expectations for governmental support and protection for female workers. This issue falls within the realm of contemporary Islamic jurisprudence (fiqh), which remains subject to scholarly debate due to the absence of explicit textual evidence. Nevertheless, based on Islamic legal principles and Indonesian positive law, women's employment is generally considered permissible (mubah).